2022
DOI: 10.4025/actasciagron.v44i1.53515
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between increased CO2 and temperature enhance plant growth but do not affect millet grain production

Abstract: The intergovernmental panel on climate change predicts a progressive increase in atmospheric CO2 concentration and temperature; however, their effects on cereals have been shown for a limited number of species. This study evaluates the effects of increased CO2 concentration and temperature separately and combined on millet growth and grain production in open-top chambers where the microclimate was adjusted to the following conditions: ambient CO2 and temperature; CO2 enriched (~ 800 ppm) and ambient temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous work has reported that the blueberry crop presents high yield instability associated with the capacity to assimilate CO 2 due to a year-to-year environmental variation [ 24 ]. Light and temperature are two of the most important environmental factors in crop production; the CO 2 is assimilated in photosynthesis and its concentration increase in the atmosphere may influence carbon uptake and assimilation rate and, therefore, plant growth [ 25 ]. Photosynthesis increases as CO 2 increases until it reaches saturating concentrations, as high CO 2 allows plants to use the light more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has reported that the blueberry crop presents high yield instability associated with the capacity to assimilate CO 2 due to a year-to-year environmental variation [ 24 ]. Light and temperature are two of the most important environmental factors in crop production; the CO 2 is assimilated in photosynthesis and its concentration increase in the atmosphere may influence carbon uptake and assimilation rate and, therefore, plant growth [ 25 ]. Photosynthesis increases as CO 2 increases until it reaches saturating concentrations, as high CO 2 allows plants to use the light more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, eCO 2 can also mitigate the effects of drought by increasing WUE and improving PSII function [ 4 , 45 ]. Moreover, in combination with temperature stress, eCO 2 can also accelerate plant growth [ 46 ]. However, both high and ultra-high concentrations of CO 2 are known to exert a negative effect on photosynthesis via drought and heat stress [ 20 , 47 ].…”
Section: Introductionmentioning
confidence: 99%